The EMS and the international monetary system: towards greater stability - SARCINELLI, M. (PSL Quarterly Review, 2013)
The European Monetary System (EMS) is an attempt to achieve greater stability of monetary relationships between member states of the European Community. The author examines the theoretical foundations of such a scheme before discussing the experience of the EMS since its establishment in 1978. Particular attention is paid to the problem of harmonising the different monetary objectives of member states within the EMS and the role of the European Currency Unit in achieving harmonisation. This leads to an analysis of how greater stability may be achieved between the EMS and other currency areas and of how international monetary stability may be improved. JEL: E42, F36